Characteristics, analysis, and potential applications of saponin as a biological surfactant from Nephelium lappaceum (Rambutan) leaves: A mini review - Yasmin Amirah, Che Yahaya; Normaiza, Zamri; Aini Norhidayah, Mohamed; Roney, Miah (International Scientific Organization, 2024)
Saponins are naturally occurring glucoside compounds found in various plant species, including the leaves of the rambutan tree. With their amphipathic structure, saponins possess a hydrophilic head and hydrophobic tails, making them capable of lowering surface tension and exhibiting solubilizing and emulsifying properties. As the demand for synthetic surfactants in diverse applications such as detergents, cosmetics, and industrial processes continues to rise, there is some interest in exploring alternative sources of surfactants. This mini review article aims to provide a comprehensive understanding of the saponins, including their characteristics, qualitative and quantitative determination, and chromatography analysis methods. Furthermore, exploring the potential applications of saponins as a biological surfactant derived from rambutan leaves, highlighting their unique properties and benefits over synthetic alternatives.